KUMAN DAN KEPEKAAN ANTIMIKROBA DI KASUS PATAH TULANG TERBUKA - Yanty Tandirogang; Tenri Esa; Nurhayana Sennang (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
About 70% of all nosocomial infections occur in surgical patients. In open fracture, there is contact with the environment or unsterilebody compartment, so that bacterial contamination may occur and cause infection. Besides debridement, prophylactic antibiotics havebeen used as a standard procedure in the open fracture management. This procedure may cause antibiotics resistance leading to increasethe number of infections. The aim of this retrospective study was to know the characteristics, microbial pattern, and sensitivity of 35cultures and sensitivity test of open fracture patients in Orthopaedics Department of Wahidin Sudirohusodo Hospital during the period ofJune 2009–June 2010. The most common bacteria found were Proteus mirabilis (26%), Klebsiella pneumonia (14. 8%), and Providenciaalcalifaciens (14%). The sensitivity test for antimicrobials showed that most of the 19 antimicrobials, were resistant. The sensitiveantimicrobial is Meropenem.